Estrogen Receptor α Signaling in Salivary Gland Tumors: Lessons Learned from Breast Carcinoma - Bashir, Nasiha (International Journal of Pathology, 2021)
Introduction: Successful antihormonal therapy in breast cancers has convinced researchers to find hormonal targets in salivary gland tumors (SGTs) due to histological and morphological similarities between the two types of glands and their tumors. The aim of this study was to determine expression of estrogen receptor (ER) α in SGTs in our region to see if the same treatment regimen may be followed in SGTs with some modifications if needed according to breast tumors.Materials and Methods: This retrospective analysis was carried out on 57 already diagnosed cases of SGTs. Cases were recruited from histopathology labs of Ayub Medical College, Peshawar Medical College and City laboratory Peshawar. All cases were examined immunohistochemically for ER α expression. Assessment was done by Allred scoring.Results: Among 57 cases of SGTs, positive hormonal expression was found in 54.4% of cases while 45.6% of cases were found negative.Conclusion: This study concluded that ER α can be considered as an attractive target for antihormonal therapy in the subset of SGTs expressing them in variable proportions.